A hybrid active power filter connected to aphotovoltaic array - Zainal, Salam, Dr.; Tan, Perng Cheng; Awang, Jusoh (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/